„egy eltemetett világ halott dicsősége”: A kollektív trauma és a gyászmunka nyomai Jókai Mór novellaciklusában (Forradalmi- és csataképek) - Bényei, Péter (Studia Litteraria, 2011)
In the recent past, the literary representations of traumatic experience have aroused the interest of social and literary studies in Hungary. The short story cycle Forradalmi- és csataképek (Pictures of Revolution and Battle), written by Mór Jókai shortly after the close of the Hungarian War of Independence of 1848-49, is well suited for analyses in the context of trauma discourse, since its rhetorical code, narrative strategies, composition and genre are all oriented towards the representation of collective trauma. The short stories also stage the successive phases of grieving: the mapping of the trauma that befell both individuals and the communal spirit, facing the loss, and the release of grief. My reading of the short stories identifies the various detraumatizing poetical actions that are most obviously detectable in the mourning process featured by the text. Collective trauma is not a directly tangible psychic wound: the major endeavour of literary narratives representing collective traumatization is to point out the very existence of the wounds affecting the communal psyche, and to remedy them in some way. Literary texts can obtain this ability primarily by merging them with the discursive spaces of plot structures, generic models offered by the tradition, and potentially evoked intertexts. Thus, my intention with the interpretation of the meta-discourses of Jókai’s short story cycle is to demonstrate the frames and media of the literary representation of trauma and the work of mourning.